Self Compacting Concrete Using Steel Slag as a Partial Replacement to Fine Aggregates (International Journal of Innovative Research in Engineering & Management, 2022)
Concrete is the most widely used material in the  building sector. Every year, hundreds of millions of cubic  meters of concrete are utilized in India alone. Concrete is  composed up of coarse and fine particles that have been  cemented together using binding material. The typical  concrete process in the construction industry is unsustainable  since it consumes large amounts of natural resources such as  sand, stone, and millions of tons of cement each year, which  is harmful to the environment. Aggregate accounts for 70- 80% of the volume of concrete and has a considerable impact  on its various properties. Even industrialized countries have  suffered aggregate supply constraints as a result of the  significant growth in concrete demand across the world. As a  result, research is needed to identify an environmentally  benign and readily available alternative to the usage of  component elements in concrete. Slag is a by-product of the  steel industry, created by impurities in the metals or ores  being processed during smelting, welding, and other  metallurgical and combustion operations. Slag is generally  made up of mixed oxides of elements including silicon,  Sulphur, phosphorus, and aluminium ash, as well as  byproducts of their interactions with furnace linings and  fluxing materials like limestone. According to estimates,  around one thousand million tonnes of slag is created as solid  waste in India alone, necessitating study into how to use this  large byproduct of the steel industry, which is not recyclable,  as one of the elements in concrete manufacturing. Steel slag in  construction protects natural aggregates while also using slag  waste from steel mills, resulting in a higher reduction in  environmental pollution. The use of steel slag as a partial substitute for fine aggregate  in different concrete mixes where varying percentages of  cement have been replaced by fly ash and metakaolin is  recommended in this study. The effect of increasing the  proportion of steel slag on various parameters was researched  and compared, as were tests on compressive strength, tensile  strength, and water absorption.
Keywords: Glass powder with calcium nitrate Abbreviations OPC (ordinary Portland cement); PCC (pozalana Portland cement); CTM (compression testing machine); LW (light weight); CSA (cross sectional area); CSS (Compressive strength of concrete)